Seasonal variability in phytoplankton light absorption properties: Implications for the regional parameterization of the chlorophyll a specific absorption coefficients. (1st January 2022) - Mercado, Jesús M.; Gómez-Jakobsen, Francisco
Abstract: Data of in vivo absorption of particulate material in water column obtained from multiple research cruises performed in the Alboran Sea (Western Mediterranean Sea) were used to investigate seasonal variability of the phytoplankton light absorption properties. Specific absorption coefficients of phytoplankton, a p h ∗ (λ) were calculated and used to determine the performance of a p h ∗ (λ) parameterizations based on chlorophyll a concentration for each season. a p h ∗ (λ) in the blue spectral bands for the euphotic layer decreased by 20% in spring and summer compared with autumn and winter. These changes might reflect stronger dominance of diatoms during these periods, since these cells are characterized by a high degree of pigment packaging that leads to flattening of the absorption spectrum. Surface temperature and salinity, which are proxies for modifications of the surface layer by vertical mixing, explained more than 50% of the variability in the absorption properties, suggesting that the communities also presented high photo-acclimation capacity in response to short-term hydrological variability. The biases between measured and parameterized a p h ∗ (λ) decreased when the seasonal relationships between chlorophyll a concentration and a p h ∗ (λ) were used for estimating the parameterization coefficients instead of using the whole dataset. The regional parameterization using seasonal data performed better that parameterizations using global data. These seasonal and regional parameterizations can be useful for developing more refined bio-optical models of primary production for the study area, although it has to be taken into account that a significant percentage of variability in a p h ∗ (λ) related to short-term hydrological changes remained still unexplained by the seasonal parameterization. Highlights: Chlorophyll  a light absorption coefficients [a*(λ)] in the spectral blue band decreased by 20% in spring and summer. Seasonal changes in phytoplankton optical properties might reflect stronger dominance of diatoms during spring and summer. Seasonal parameterizations improved the estimation of a*(λ) in comparison to the available global parameterizations.